Penatalaksanaan Self Efficacy dengan Peran Keluarga Dalam Merawat Pasien Skizofrenia di Wilayah Kerja Puskesmas Kuranji - Gusdiansyah, Edo; Welly (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2024)
Having a family member with schizophrenia (ODS) is still one of the problems of mental illness that has an impact on psychological conditions, mental health, burden and family roles. Efforts to cure people with schizophrenia cannot be done alone, but require the role of the family in caring for them. The family plays a supportive role during the healing and recovery period, if the role is not fulfilled, the success of healing or recovery will be less. To support the success of the family role in caring, it is necessary to do is self efficacy related to the ability to cope with problems, stress and problem solving in caring for family members with schizophrenia. The purpose of this community service is Self-Efficacy Management with Family Role in Caring for Schizophrenia Patients in the Kuranji Community Health Centre Work Area Padang. Based on the results of community activities obtained data on family roles 78% good, self efficacy 80% good in caring for family members with schizophrenia after health education.